A Comparison Study on the Removal of Phenol From Aqueous Solution Using Organomodified Bentonite and Commercial Activated Carbon - Mostafa Leili; Javad Faradmal; Farzaneh Kosravian; Mahdieh Heydari (Hamadan University of Medical Sciences, 2015)
The potential of bentonite modified with cationic surfactant (CTAB-Bent) and commercial Activated Carbon (AC) for the removal of phenol removal was assessed. Batch kinetics and isotherm studies were carried out to evaluate the effects of contact time (t), phenol initial concentration (C0), adsorbent dose (Cads), and pH of the solutions. Kinetics and isotherm of the adsorption were also determined using the most frequent models. The results of the study showed that increasing C0 could result in the increase of adsorption capacity of both types of adsorbents. The optimum pHs for CTAB-Bent and AC were determined as 10 and 8, respectively. The equilibrium data of the phenol adsorption from the aqueous solutions was well fitted by the Langmuir isotherm models. The kinetics study revealed that pseudo-second-order kinetics gives better description of adsorption process. The adsorption capacities, as deduced from the adsorption isotherm were 22.68 and 112.36 mg/g for CTAB-Bent and activated carbon, respectively. However, considering the market price of these adsorbents, low-cost modified bentonite can be a promising adsorption technology and an alternative adsorbent to commercial activated carbon in the future.